Long-term Performance Evaluation and Economic Analysis for Deep Borehole Heat Exchanger Heating System in Weihe Basin - Cai, Wanlong; Wang, Fenghao; Jiang, Jinghua; Wang, Zeyuan; Liu, Jun; Chen, Chaofan (Frontiers in Earth Science, 2022)
To reduce carbon emission and achieve carbon neutrality, deep geothermal energy has been widely extracted for building heating purpose. In recent years, Deep Borehole Heat Exchanger (DBHE) heating system has gained more attention, especially in densely populated urban areas in Weihe Basin, northern China. The long-term performance and the economic feasibility are essential for the system application. In this work, the DBHE model implemented in OpenGeoSys software is verified against an analytical solution and a comprehensive economic analysis approach is further proposed. Then the short-term thermal performance tests are conducted to obtain the tentative heat extraction capacity for long-term simulation. The long-term simulations are further performed with the heat pump unit under the adjusted tentative heat extraction rate imposed on the DBHE. Finally, a comprehensive economic analysis is applied to the DBHE heating system over 15 heating seasons. Results show that the minimum Coefficient of Performance (COP) value of the heat pump is 4.74 over the operation of 15 heating seasons. With the increase of depth for the DBHE, the total electricity consumption of heat pumps and circulation pumps has a prominent promotion. With the comprehensive approach of economic analysis, the depth of 2600 m has the lowest Levelized cost of total heating amount (LCOH), which is the best system design for the application in Weihe Basin. The present results are specific to the conditions in Weihe basin but the proposed economic analysis approach is generic.